THE ROLE OF DIGITAL TECHNOLOGIES IN IMPROVING THE EFIICIENCY OF SMALL BUSINESS IN UZBEKISTAN - Abdullayeva, Dilnoza Bakhodir kyzy (THE INNOVATION ECONOMY, 2026)
The rapid advancement of modern technologies has significantly influenced the development of business activities around the world. In particular, the integration of digital technologies into small business operations has become an important factor in improving efficiency, competitiveness, and sustainability. Small businesses play a crucial role in economic growth by generating employment, stimulating innovation, and supporting the diversification of national economies. Therefore, studying the impact of digital technologies on the efficiency of small business activities is of great scientific and practical importance.